2017
DOI: 10.1177/1088868317721372
|View full text |Cite
|
Sign up to set email alerts
|

The Happy Culture: A Theoretical, Meta-Analytic, and Empirical Review of the Relationship Between Culture and Wealth and Subjective Well-Being

Abstract: Do cultural values enhance financial and subjective well-being (SWB)? Taking a multidisciplinary approach, we meta-analytically reviewed the field, found it thinly covered, and focused on individualism. In counter, we collected a broad array of individual-level data, specifically an Internet sample of 8,438 adult respondents. Individual SWB was most strongly associated with cultural values that foster relationships and social capital, which typically accounted for more unique variance in life satisfaction than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
136
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(173 citation statements)
references
References 329 publications
(434 reference statements)
17
136
3
3
Order By: Relevance
“…It is important to note that meta‐analytic correlations derived from metaBUS are similar to meta‐analytic correlations derived from other academic databases (Lee, Bosco, Steel, & Uggerslev, ; Steel, Taras, Uggerslev, & Bosco, ). One study that utilized metaBUS derived meta‐analytic correlations on career satisfaction and compared the findings with previously published meta‐analytic findings, confirmed the relative sizes of the effects as well as the direction of the effects (Lee et al).…”
Section: Metabus As Search Engine For Supplemental Data For Secondarysupporting
confidence: 58%
See 1 more Smart Citation
“…It is important to note that meta‐analytic correlations derived from metaBUS are similar to meta‐analytic correlations derived from other academic databases (Lee, Bosco, Steel, & Uggerslev, ; Steel, Taras, Uggerslev, & Bosco, ). One study that utilized metaBUS derived meta‐analytic correlations on career satisfaction and compared the findings with previously published meta‐analytic findings, confirmed the relative sizes of the effects as well as the direction of the effects (Lee et al).…”
Section: Metabus As Search Engine For Supplemental Data For Secondarysupporting
confidence: 58%
“…One study that utilized metaBUS derived meta‐analytic correlations on career satisfaction and compared the findings with previously published meta‐analytic findings, confirmed the relative sizes of the effects as well as the direction of the effects (Lee et al). Another study used metaBUS to check the validity of the intercorrelations derived based on a literature search utilizing several academic databases (Steel et al, ). Findings indicated that metaBUS derived intercorrelations closely approximated the intercorrelations derived from the literature search with an average difference of 0.07 and an absolute average difference of 0.09 (Steel et al).…”
Section: Metabus As Search Engine For Supplemental Data For Secondarymentioning
confidence: 99%
“…Even these concepts are used for each other's, but there are some differences between these concepts regarding meaning and content (Camfield & Skevington, ; Diener, Oish, & Tay, ; Keser, ; Saris, Veenhoven, Scherpenzeel, & Bunting, ). Especially subjective well‐being is a key component of quality of life (Diener & Ryan, ) and it also combines satisfaction and happiness (Steel, Taras, Uggerslev, & Bosco, ). Thus, it is not easy to separate these concepts from each other exactly.…”
Section: Discussionmentioning
confidence: 99%
“…The religiosity and materialism were inversely related, whereby religious people tend to become less materialistic (Bakar et al, 2013). Value from financial success is different from the feminine value that is related with modesty, caring, harmony and a focus on improving the quality of life (Steel et al, 2018).…”
Section: Hypothesis Developmentmentioning
confidence: 98%